Correlation between Parity and Maternal Attitudes with the Contraception of Post-Child Birth use in the Mranggen Health Center - Siti Nurjanah; Shela Aliyana Nafisatus Sa’diyah; Mindiatussholihah Mindiatussholihah (Jurnal Kebidanan, 2024)
Background: Birth control given to the recipient for 42 days after delivery is known as post-partum birth control. Data from BKKBN shows that 42% of pregnancies occur between 12 and 25 months of gestation, and if pregnancy occurs too soon after delivery, postnatal birth control reduces AKI. In the Demak district in 2021, as many as 252,125 people participated in active family planning programs (84.1%). Meanwhile, there will be an increase in the number of women of childbearing age in 2022, namely 253,663 people. Still, those who actively participate in family planning have not increased by a percentage of 80.9%. Objective: research to determine the characteristics and relationship between parity and maternal attitudes with the use of postpartum family planning in the working area of the Mranggen Health Center. Method used is descriptive and cross-sectional. The sample consisted of 60 people using proportional random sampling. Results analysis shows that the highest age group is 48 people (80.0%) with an age range of 20-30 years, the mother’s education is (48.3%) and the highest data is for mothers with a Bachelor’s degree, amounting to 29 people. Maternal employment was found to be the highest percentage of 33 mothers who did not work (55.0%), while the parity of mothers with a high percentage of primiparas (53.3%) was 32 people compared to multiparas. The results of bivariate analysis on the variables age p-value 0.027 (<0.05), education p-value 0.000 (<0.05), parity p-value 0.007 (<0.05), attitude p- value 0.003 (<0, 05) is related to the use of postpartum birth control and work p-value 0.653 (>0.05) there is no relationship with postpartum birth control. Conclusion, there is a relationship between age, education, parity, and the mother’s attitude towards the use of postpartum contraception. Meanwhile, employment has no relationship with postpartum birth control use.